2019
DOI: 10.1590/s0004-2803.201900000-04
|View full text |Cite
|
Sign up to set email alerts
|

Is the Physician Expertise in Digital Rectal Examination of Value in Detecting Anal Tone in Comparison to Anorectal Manometry?

Abstract: BACKGROUND: Digital rectal examination (DRE) is part of the physical examination, is also essential for the colorectal surgeon evaluation. A good DRE offers precious information related to the patient’s complaints, which will help in decision making. It is simple, quick and minimally invasive. In many centers around the world, the DRE is still the only method to evaluate the anal sphincter prior to patient’s management. On the other hand, anorectal manometry (ARM) is the main method for objective functional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
4
1
1
Order By: Relevance
“…The correlation between the surgeons' DRE, pelvic floor physical therapists' DRE, and the 3D-HRAM in our study was moderate and somewhat better for squeeze tone/pressures than resting tone/pressures. Several studies compared DRE with ARM and showed an overall good agreement of pressures, however similar to our study, slightly better for squeeze pressures, but results are not consistent [9,15,[34][35][36][37][38][39]. For example, the study by Beatrice et al showed that DRE correlates well, but not perfectly, with the ARM for resting pressures, (r = 0.71 (p < 0.001) [9].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The correlation between the surgeons' DRE, pelvic floor physical therapists' DRE, and the 3D-HRAM in our study was moderate and somewhat better for squeeze tone/pressures than resting tone/pressures. Several studies compared DRE with ARM and showed an overall good agreement of pressures, however similar to our study, slightly better for squeeze pressures, but results are not consistent [9,15,[34][35][36][37][38][39]. For example, the study by Beatrice et al showed that DRE correlates well, but not perfectly, with the ARM for resting pressures, (r = 0.71 (p < 0.001) [9].…”
Section: Discussioncontrasting
confidence: 63%
“…In contrast, Soh et al described a poor agreement between DRE and ARM for resting pressures with a k coefficient of 0.01 and a moderate agreement for squeeze pressure with a k coefficient of 0.42 [ 35 ]. Pinto et al showed a moderate to strong agreement for resting pressure with a Gamma index of 0.7 and a strong correlation of the squeeze pressures with a Gamma of 0.96 [ 37 ]. All studies—including ours—report that the examinations were performed by experienced examiners but the results vary considerably.…”
Section: Discussionmentioning
confidence: 99%
“…Ce score est critiquable, non pas tant dans sa dimension « tonique » que dans celui testant la force musculaire, car les scores « supra-normaux » sont difficilement envisageables. D'une manière générale l'examen du tonus et de la motricité anale sont plutôt en accord avec les données manométriques [8,9,10], ce qui n'est pas confirmé par toutes les études [11,12,13,14] notamment en termes de sensibilité et en particulier chez les médecins juniors [13].…”
Section: L'évaluation Du Tonus Analunclassified
“…Additionally, DREs are subjective tests and the degree of precision depends on the examiner's experience [ 8 ]. In a meta-analysis, DRE has shown a sensitivity and a positive predictive value (PPV) of 17.8% for PCa [ 6 ].…”
Section: Introductionmentioning
confidence: 99%